The role of cellular RNA decay pathways in Sindbis virus infection - Garneau, Nicole L., author; Wilusz, Jeffrey, advisor; Wilusz, Carol, advisor (Colorado State University. Libraries, 2009)
Sindbis virus is the prototypic species of the Alphavirus genus. Members of this genus can cause febrile illness, arthritic pain and potentially fatal encephalitis. The alphaviral lifecycle generates single-stranded, positive-sense genomic and subgenomic RNAs which are capped on the 5' terminus, contain 5' and 3' untranslated regions (UTRs), and are polyadenylated at the 3' terminus. These characteristics make alphaviral RNAs similar in structure to cellular mRNAs. Such features allow alphaviruses, such as Sindbis, to benefit from the host cell translation process; however, they also could make the viral transcript vulnerable to the cellular mRNA decay enzymes. mRNA decay is a form of post-transcriptional regulation of gene expression found in both mammalian and mosquito hosts of Sindbis virus. The interaction between Sindbis viral RNAs and mRNA decay pathways was investigated in this dissertation. Using a novel in vivo viral RNA decay assay to accurately assess the rate of alphavirus RNA decay during infection, we found a correlation between Sindbis viral RNA stability and viral replication efficiency, demonstrating mRNA decay potentially represents a novel host cell restriction factor. We established that the RNAi pathway likely plays a dominant role in the decay of the viral RNAs during infection in mammalian cells. These data represent a novel demonstration that the RNAi pathway is potentially an effective antiviral response in the mammalian host as it is in the mosquito host. With the development of a highly sensitive method to assess poly(A) tail length, we were able to demonstrate the importance of the viral 3'UTR as a repressor of deadenylation of viral RNAs in vivo. Lastly, we found that Repeat Sequence Element 3 (RSE 3), the third and final in a series of three RSEs within the viral 3'UTR, hinders the processivity of the cellular deadenylases on viral RNAs in vitro, providing the first evidence for a function of this conserved alphaviral genome element. Taken together, these results shed light on the much understudied area of viral RNA decay. Our data support the notion that the interaction between viral RNAs and the cellular RNA decay machinery is very important to the biology of the virus.
Keywords: alphavirus; RNA decay; RNAi; Sindbis virus; molecular biology; virology